A nurse‐led model at public academic hospitals maintains high adherence to colorectal cancer surveillance guidelines. Issue 11 (11th June 2018) - Symonds, Erin L; Simpson, Kalindra; Coats, Michelle; Chaplin, Angela; Saxty, Karen; Sandford, Jayne; Young AM, Graeme P; Cock, Charles; Fraser, Robert; Bampton, Peter A
Abstract: Objective: To examine the compliance of colorectal cancer surveillance decisions for individuals at greater risk with current evidence‐based guidelines and to determine whether compliance differs between surveillance models. Design: Prospective auditing of compliance of surveillance decisions with evidence‐based guidelines (NHMRC) in two decision‐making models: nurse coordinator‐led decision making in public academic hospitals and physician‐led decision making in private non‐academic hospitals. Setting: Selected South Australian hospitals participating in the Southern Co‐operative Program for the Prevention of Colorectal Cancer (SCOOP). Main outcome measures: Proportions of recall recommendations that matched NHMRC guideline recommendations (March–May 2015); numbers of surveillance colonoscopies undertaken more than 6 months ahead of schedule (January–December 2015); proportions of significant neoplasia findings during the 15 years of SCOOP operation (2000–2015). Results: For the nurse‐led/public academic hospital model, the recall interval recommendation following 398 of 410 colonoscopies (97%) with findings covered by NHMRC guidelines corresponded to the guideline recommendations; for the physician‐led/private non‐academic hospital model, this applied to 257 of 310 colonoscopies (83%) ( P < 0.001). During 2015, 27% of colonoscopies in public academic hospitals (mean, 27 months; SD, 13 months) and 20% of those in private non‐academic hospitals (mean, 23 months; SD, 12 months) were performed more than 6 months earlier than scheduled, in most cases because of patient‐related factors (symptoms, faecal occult blood test results). The ratio of the numbers of high risk adenomas to cancers increased from 6.6:1 during 2001–2005 to 16:1 during 2011–2015. Conclusion: The nurse‐led/public academic hospital model for decisions about colorectal cancer surveillance intervals achieves a high degree of compliance with guideline recommendations, which should relieve burdening of colonoscopy resources.